Research on the penetration resistance characteristics of 2024-T42 aluminum alloy tube to spherical steel projectes - WANG Ligang; WANG Rihan; XIAO Siwei; TIAN Lu; DONG Qin (Jixie qiangdu)
MethodsThe finite element model of spherical steel projectile penetrating 2024-T42 aluminum alloy target was established based on Ansys/Workbench software and Johnson-Cook material model, and its effectiveness was verified. In addition, the response characteristics of aluminum alloy circular tubes with different radii and thicknesses under normal impact of spherical steel bullets were simulated, and the deformation and damage of the circular tubes were analyzed.ResultsThe results show that the anti penetration ability of the upper and lower walls of aluminum alloy circular tubes is different, and the anti penetration ability of the upper convex structure wall is better than that of the lower concave structure wall; The smaller the radius of an aluminum alloy circular tube, the better the anti penetration performance of its upper pipe wall, while the lower pipe wall is weaker than the upper pipe wall, and its ballistic limit velocity difference gradually weakens with the radius; For aluminum alloy circular pipes with the same radius, the thicker they are, the more linearly the ballistic limit velocity of the upper and lower pipe walls increases.